2020
DOI: 10.1186/s13102-020-00206-8
|View full text |Cite
|
Sign up to set email alerts
|

Thai version of the foot function index: a cross-cultural adaptation with reliability and validity evaluation

Abstract: Background The study aimed to translate the foot function index (FFI) questionnaire to Thai and to determine psychometric properties of the questionnaire among individuals with plantar foot complaints. Methods The Thai version of the FFI (FFI-Th) was adapted according to a forward and backward translation protocol by two independent translators and analyzed by a linguist and a committee. The FFI-Th was administered among 49 individuals with plantar foot complaints to determine internal consistency, reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The FFI-Arb demonstrated excellent internal consistency for pain and disability but had good internal consistency for activity limitation. These results are similar to previous findings that reported that the activity limitation domain had good internal consistency, while the pain and disability domains demonstrated excellent internal consistency [ 23 , 24 , 34 , 39 , 40 ]. However, few studies, such as the cross-cultural adaptation the Danish [ 38 ] and Chinese versions [ 32 ], have reported excellent internal consistency in all three domains of FFI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The FFI-Arb demonstrated excellent internal consistency for pain and disability but had good internal consistency for activity limitation. These results are similar to previous findings that reported that the activity limitation domain had good internal consistency, while the pain and disability domains demonstrated excellent internal consistency [ 23 , 24 , 34 , 39 , 40 ]. However, few studies, such as the cross-cultural adaptation the Danish [ 38 ] and Chinese versions [ 32 ], have reported excellent internal consistency in all three domains of FFI.…”
Section: Discussionsupporting
confidence: 91%
“…The study also reported a high correlation between the German-version of FFI with a Short form health survey of 36 items [ 24 ]. Similar results have been reported in articles involving translation and cross-culturally adapted FFI questionnaires in Spanish [ 33 ], Thai [ 34 ], Brazilian Portuguese [ 35 ], Korean [ 36 ], and Chinese [ 37 ] reported good to excellent test-retest reliability. A study conducted among 35 Danish-speaking populations reported that the Danish version of FFI is a reliable and valid instrument for foot-related disorders [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Second, the FAOS and FFI-5pt showed, respectively, ceiling and floor effects in our cohort. These effects have been previously reported, 18,20 and this has to be taken into account when interpreting the median scores which were often 100 and 0, respectively. We therefore also report the number of participants in the bottom half of the score, and have shown that this was the case for a substantial number of patients.…”
Section: Discussionmentioning
confidence: 60%
“…Aggregated scores range from 0 to 100 for pain, activity and total; the higher the score, the more limitation or pain is present. For the FOAS floor effects have been reported up to 10%, thus floor effects will also be reported 20 . To the best of our knowledge, no cut-off scores for the FAOS or FFI-5pt have been published.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation